2016
DOI: 10.1371/journal.pbio.1002411
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Ammonia-Permeable Aquaporin

Abstract: Aquaporins of the TIP subfamily (Tonoplast Intrinsic Proteins) have been suggested to facilitate permeation of water and ammonia across the vacuolar membrane of plants, allowing the vacuole to efficiently sequester ammonium ions and counteract cytosolic fluctuations of ammonia. Here, we report the structure determined at 1.18 Å resolution from twinned crystals of Arabidopsis thaliana aquaporin AtTIP2;1 and confirm water and ammonia permeability of the purified protein reconstituted in proteoliposomes as furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 39 publications
5
133
0
4
Order By: Relevance
“…To evaluate structural similarities and differences, theoretical models for EgTIPs representing each classical TIP group were constructed using a comparative modeling approach and the crystallography structure of AtTIP2.1 at 1.18Å resolution (Kirscht et al, 2016) as a template. The sequences shared 53–85% aa identity and 90–95% of coverage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate structural similarities and differences, theoretical models for EgTIPs representing each classical TIP group were constructed using a comparative modeling approach and the crystallography structure of AtTIP2.1 at 1.18Å resolution (Kirscht et al, 2016) as a template. The sequences shared 53–85% aa identity and 90–95% of coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Further comparison of the EgTIP-deduced aa sequences with those of other plant TIPs revealed that TIP members of groups 1 and 2 have the most conserved selectivity filters, including the H residue located in loop C (LC) of the proposed extended ar/R filter (Kirscht et al, 2016) ( Figures 3D,E ). VvTIP1.3 from V. vinifera , that possesses an M residue instead of a V in the LE2 position, is the only exception.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations